Herbal Plants: A Potential Agent to Cure Infectious Mastitis in Bovine Animals - Reena Patel; Yogesh Patel; Anju Prasant Kunjadia (International Journal of Phytomedicine, 2013)
The medicinal plants are used in traditional treatments in order to cure variety of diseases since prehistoric period. Bovine mastitis is an inflammation of mammary gland and it is the most serious and economically important disease in the dairy milk production worldwide. The main aim of this study was to identify such plants with antimicrobial efficacy against some mastitis pathogens. For this purpose the locally available plants viz., Gymnema sylvestre, Holarrhena antidysenterica, Vernonia anthelmintica Enicostemma littorale, Momordica charantia, Swertia chirata, Azadirachta indica, Caesalpinia bonducella were selected for the study. These plants were screened against 18 bacteria that were isolated from clinical and sub clinical milk samples of buffaloes. The plants were extracted using methanol and showed the inhibitory effect against gram- positive and gram-negative bacteria. But gram-positive bacteria are more sensitive than gram-negative bacteria. The largest zone of inhibition [24mm in diameter] was recorded against corynebacterium xerosis with the leaf extract of Azadirchta indica. It was concluded that these plant extract can be used as a drug against the mastitis causing pathogens.